Dictionary of French family names in North America : onomastics and genealogy - Picard, Marc (Cambridge Scholars Publishing, 2020)
"This dictionary contains data not only on the origins of French surnames in Québec and Acadia, a great many of which eventually spread to many parts of North America, but also on those which arrived in the United States directly from various French-speaking European and Caribbean countries. In addition to providing the etymology of the original surnames, it also lists the multifarious variants that have developed over the last four centuries. A unique feature of this work in comparison to other onomastics dictionaries is the inclusion of genealogical information on most of the Francophone migrants to this continent, something which has been rendered possible not only by the excellent record-keeping in French Canada since the very beginnings of the colony, but also through the explosion of such data on the internet in the last couple of decades. In sum, this dictionary serves the dual purpose of providing information on the meanings of French family names on the North American continent, as well as on the migrants who brought them there" --Provided by publisher.